Quantification of oleanolic acid and apigenin in biological matrices following intraperitoneal administration of co-loaded nanoformulations: Method validation and biodistribution studies - Amna Naz; Sadia Haider; Mavra Rana; Neelum Malik; Attia Afzal; Muhammad Farooq; Muhammad Sarfraz (Talanta Open)
Oleanolic acid (OA) and apigenin (APG) demonstrate a wide range of pharmacological effects, including antioxidant, anti-inflammatory, antiviral, antidiabetic, hepatoprotective, and cardioprotective activities. Both compounds show anticancer potential and have been used individually to treat various cancer types, creating a rationale for their combined use. However, quantifying both drugs in quality and plasma samples presents challenges due to differences in their physicochemical properties and absorption wavelengths (OA: 210–215 nm, APG: 212, 269, and 337 nm). We developed and validated a novel High-Performance Liquid Chromatography UV detection (HPLC-UV) method to address this problem. Using a C18 column (4.6 mm x 250 mm, packing L1, 5 µm particle size) and a mobile phase of acetonitrile: methanol: tetrahydrofuran: water (60:20:8:12, v/v) with a detection wavelength of 215 nm. The method achieved retention times of 4.7 and 10 minutes for OA and APG in quality samples, and 4.9 and 9.8 minutes in plasma samples, respectively. The plasma sample was prepared by simple protein precipitation step. All validation parameters, including sensitivity, selectivity, precision, accuracy, robustness, and stability, met the required criteria. The validated HPLC-UV bioanalytical method was effectively applied in quantification, stability, and pharmacokinetic studies of co-loaded nanoformulations of OA and APG with particle size 163 nm. The entrapment efficiency for OA was 93.95 ± 3.50 %, and for APG, it was 94.5 ± 2.31 % in combined nanoformulation, establishing it as a promising analytical technique for detecting these anticancer agents in complex matrices such as blood, plasma, and polymeric systems.